1984
DOI: 10.1007/bf01972376
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of Panax Ginseng C.A. Meyer in the mouse

Abstract: An aqueous extract of Panax Ginseng C.A. Meyer (G.S.) was prepared by boiling crushed G.S. roots in water. The extract obtained was adjusted to 125 mg G.S. per ml and was administered orally to mice for 5 to 6 days at the daily dose of 10, 50 and 250 mg G.S. per kg or was added to cultures of mouse spleen cells at concentrations varying between 0.25 and 8 mg G.S. per ml. The average total ginsenoside content of the G.S. roots used was determined by HPLC analysis and found to be 0.58% (w/w). Treated mice respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 7 publications
2
60
0
2
Order By: Relevance
“…Saponins reportedly induce production of cytokines such as interleukins and interferons that might mediate their immunostimulant effects (Jie et al, 1984;Kensil, 1996). It is likely that they interact with antigenpresenting cells to induce many of these responses (Barr et al, 1998).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponins reportedly induce production of cytokines such as interleukins and interferons that might mediate their immunostimulant effects (Jie et al, 1984;Kensil, 1996). It is likely that they interact with antigenpresenting cells to induce many of these responses (Barr et al, 1998).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Ginsenoside Rg1 has been found to increase the lymphocyte proliferative responses to mitogenic stimulation and IL-2 production in aged rats but not in young rats (Liu and Zhang, 1995; and human . Ginseng extract has also been reported to enhance, specific antibody response against diphtheric toxoids in mice (Yang et al, 1983); increase IgG and IgM antibody responses in mice immunized with sheep red blood cells and oral administration of ginseng extract at the same time (Jie et al, 1984). Sun et al(2006a) reported the ovalbumin (OVA) specific IgG, IgG1, IgG2a and IgG2b antibody levels in serum were significantly enhanced by seven PTS from the root of Panax notoginseng compared with OVA control group (P<0.01 or P<0.001).…”
Section: Ginsengmentioning
confidence: 99%
“…120) This fraction activates macrophages against Candida albicans 121 , potentiates anti-complement activity, 122) induces IFN-γ and TNF-α production in lymphocytes and peritoneal macrophages, 123,124) stimulates phagocytosis in polymorphonuclear leukocytes, 125) stimulates natural killer-cell activity 126) and activates compo-nents of cell-mediated immunity 127) including interleukin-2 (IL-2) expression. 128) Of polysaccharides from Panax ginseng, acidic polysaccharides (Ginsan) induce expression of mRNA for IL-2, IFN-γ, IL-1, and GM-CSF, as well as lymphokine-activated killer (LAK) cells and CD8+T cells.…”
Section: Acidic Polysaccharidementioning
confidence: 99%
“…18 In some studies, they induced the production of cytokines such as interferons and interleukins. 19,20 The immunostimulant activity of saponins may be based on aldehyde groups or branched sugar chains 21 or an acyl residue bearing the aglycone. 20 The immunomodulatory effects of herbal plant polysaccharides have also been widely studied.…”
mentioning
confidence: 99%